The Dobbs ruling and surroundings. Pessimistic notes on the problematic “direction” taken by the current united states Supreme Court’s majority (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Starting from the recent Dobbs ruling, in which the U.S. Supreme Court overruled Roe v. Wade, the 1973 landmark decision which affirmed the federal constitutional right to abortion under the substantive component of the XIV Amendment due process clause, as well as from a number of other recent U.S. Supreme Court’s rulings on fundamental rights, the essay makes a critical overall reflection on the originalist methodological approach adopted by the current majority of the Supreme Court. Reasoning on the overall evolution of the historical, political and ideological context that has led to such recent outcomes, one wonders what could be the future jurisprudential development in various jurisprudential areas, potentially leading to other sea changes in established judicial doctrines – especially through the discard of settled multifactor balancing tests in favour of more rigid text/history/tradition based tests – mainly in a direction of lowering the standard of protection of fundamental rights. The article also reflects on the possible negative consequences on the institutional legitimacy of the Supreme Court resulting from the excessive politicisation of its work, which have already taken place in light of the swift and strong conservative turn, in particular after Dobbs.
Keywords: United States Supreme Court; substantive due process and right to abortion; constitutional interpretation; conservative legal movement; originalism/living constitutionalism